NOT JUST DEATH AND RUINS: THE YOUNG, AND NEW BEGINNINGS IN GERMAN 'RUBBLE FILMS'. (October 2016) - Wölfel, Ute
ABSTRACT: The article looks at 'Trümmerfilme' from different zones of occupation and discusses the roles which the young were allocated on German post‐war screens. While in all films under‐age characters are central to negotiating the severe national crisis following the end of World War II and the defeat of the Nazi dictatorship, the analysis highlights emerging differences in the depiction of the young between films from the Soviet Zone and the Western zones of occupation. Despite the general use of the young as figures of distraction from the adults' involvement in Nazi crimes, children in films from the Soviet Zone help to articulate a new national ideal based on collective, public productivity, while the young in films from the Western zones help to formulate the dangers inherited from the immediate past. These differences are reflected in the opposing depictions of the young as innocent in the East and feral in the West, as well as in the intergenerational relations resulting from this. While the children's potential in the East replaces the parent generation, which is implicitly marked as guilty, the dangers posed by the young in the West strengthen the authority of the parents and the nuclear‐family model. Der Aufsatz untersucht Trümmerfilme aus den verschiedenen Besatzungszonen und diskutiert die Rollen, die Kindern und Jugendlichen auf den deutschen Kinoleinwänden zwischen 1945 und 1949 gegeben wurden. Während Minderjährige in allen Filmen eine wichtige Rolle spielen bei der Aufarbeitung der nationalen Krise nach dem Ende des Zweiten Weltkriegs und der Niederlage der NS Diktatur, stellt die Analyse auch Unterschiede heraus, die sich in der Darstellung von Kindern und Jugendlichen zwischen den Filmen der SBZ und jenen der westlichen Zonen bereits abzeichnen. Ungeachtet der allgemeinen Verwendung von Kindern als Figuren der Ablenkung von der Einbindung der Erwachsenenwelt in die Verbrechen des Nationalsozialismus, helfen Kinderfiguren in Filmen aus dem Osten ein neues Ideal zu formulieren, das auf öffentlicher, kollektiver Produktivität beruht, wogegen Jugendliche in Filmen der westlichen Zonen die gefährliche Hinterlassenschaft der unmittelbaren Vergangenheit verkörpern. Diese Unterschiede schlagen sich nieder in der entgegengesetzten Darstellung von Kindern als unschuldig im Osten und gefährlich im Westen, sowie in dem daraus resultierenden Generationenverhältnis: Während das Potential der Kinderfiguren im Osten eine implizit schuldige Elterngeneration ersetzt, werden im Westen die Elterngeneration und das Kleinfamilienmodell durch die Gefährdung, die von den Jugendlichen ausgeht, gestärkt.